2016
DOI: 10.4102/jsava.v87i1.1348
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire survey on diseases and problems affecting sheep and goats in communal farming regions of the Eastern Cape province, South Africa

Abstract: A questionnaire of 15 questions was completed by four categories of respondents with the aim of establishing the experience and opinions of these groups on the constraints including animal health problems for communal, small-scale sheep and goat farming in the Eastern Cape province of South Africa. The questionnaires were completed independently and categories were representative of the areas investigated. Analysis of responses was done by means, ranges, votes and clusters of responses. Comparisons between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Various papers underline how limited access to veterinary services is a major problem for livestock producers in sub-Saharan countries: see the issues of the OIE review dedicated to Veterinary institutions in the developing world: current status and future needs with a special focus on SSA countries in 2004 and the issue Good governance and financing of efficient veterinary services in 2012; as well as the recent review of Abakar et al ( 32 ) on the status of veterinary services in the Sahel over the last 20 years. Other studies focus on a specific country or group of countries such as Kenya and Uganda ( 47 50 ), Tanzania ( 51 ), Central Africa ( 52 ), South Africa ( 53 , 54 ), or Tanzania, Uganda, and Ethiopia ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various papers underline how limited access to veterinary services is a major problem for livestock producers in sub-Saharan countries: see the issues of the OIE review dedicated to Veterinary institutions in the developing world: current status and future needs with a special focus on SSA countries in 2004 and the issue Good governance and financing of efficient veterinary services in 2012; as well as the recent review of Abakar et al ( 32 ) on the status of veterinary services in the Sahel over the last 20 years. Other studies focus on a specific country or group of countries such as Kenya and Uganda ( 47 50 ), Tanzania ( 51 ), Central Africa ( 52 ), South Africa ( 53 , 54 ), or Tanzania, Uganda, and Ethiopia ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…A structured questionnaire and visual observations were used to investigate and collect information on the production and management systems applied to indigenous Tswana sheep from a total of 105 households in the four districts of southern Botswana namely; Kgatleng ( n = 30), Kweneng ( n = 27), southern ( n = 24) and south–east ( n = 24). The questionnaire was a slightly modified version of those designed and recommended for livestock breed surveys in Africa [ 11 , 12 ]. The questionnaire included socio-economic parameters (demographic) (e.g., gender, age, marital status and education level of indigenous Tswana sheep farmers), breeding management and methods of watering sheep, feeds and feeding management of the sheep, selection criteria and major production systems of each respondent in each district.…”
Section: Methodsmentioning
confidence: 99%
“…Hossain et al, (2018) found that lack of technical knowledge and training, pasture land and high cost of vitamin mineral supplementation of selected farmers in their studied areas. Bath et al (2016) showed that average lack of information for famers, lack of training and lack of expert assistance were 9.70, 9.20 and 8.80, respectively.…”
Section: Problems Constraints and Solution Related To Sheep Farmingmentioning
confidence: 99%